Orthodontic Treatment Need and Complexity among Nigerian Adolescents in Rivers State, Nigeria - Aikins, Elfleda Angelina (Hindawi Publishing Corporation, 2011)
Introduction. The assessment of orthodontic treatment need and complexity are necessary for informed planning of orthodontic services. The aim of this cross-sectional study was to assess these parameters using the Index of Complexity, Outcome, and Need (ICON) in a Nigerian adolescent population in a region where orthodontic services are just being established. Methods. Six hundred and twelve randomly selected Nigerian adolescents aged 12 to 18 years were examined using the ICON in their school compounds. Descriptive statistics were employed in the data analysis. Results. Out of a total of 38.1% of the population found to need orthodontic treatment, there were more males and older adolescents. The overall mean ICON score for the population was 39.7 ± 25.3 SD with males having statistically higher mean ICON score. The grades of complexity of the population were 21.6% for very difficult and difficult, 7.5% moderate, and 70.9% mild/easy. Conclusions. Although just over a third of the adolescents were found to have a need for treatment, about a quarter of them were found to have difficult and very difficult complexity grades indicating a need for specialist care. The authors recommend the training of more specialist orthodontists in this region.